2014
DOI: 10.1186/1756-0500-7-334
|View full text |Cite
|
Sign up to set email alerts
|

Potential regenerative rehabilitation technology: implications of mechanical stimuli to tissue health

Abstract: BackgroundMechanical loads induced through muscle contraction, vibration, or compressive forces are thought to modulate tissue plasticity. With the emergence of regenerative medicine, there is a need to understand the optimal mechanical environment (vibration, load, or muscle force) that promotes cellular health. To our knowledge no mechanical system has been proposed to deliver these isolated mechanical stimuli in human tissue. We present the design, performance, and utilization of a new technology that may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 91 publications
1
11
0
Order By: Relevance
“…We previously confirmed that the vibration intervention mimicked the mechanical input conditions of previous animal studies [19] and that it did not cause reflexive muscle contractions [30, 31]. We used a novel and sophisticated imaging approach to obtain outstanding imaging resolution for in vivo bone adaptations.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…We previously confirmed that the vibration intervention mimicked the mechanical input conditions of previous animal studies [19] and that it did not cause reflexive muscle contractions [30, 31]. We used a novel and sophisticated imaging approach to obtain outstanding imaging resolution for in vivo bone adaptations.…”
Section: Discussionsupporting
confidence: 59%
“…The trained leg was the dominant limb for three participants and the non-dominant limb for the other three individuals. The linearity, repeatability, accuracy, and transmissibility of vibration for this system have been previously described [19]. A compressive pre-load of 10–15%of body weight (%BW)was applied to the top of the knee to couple the limb segment to the vibrating surface, after which a cyclical load of 35 % of body weight was applied (5 s on and 10 s off) during the continuous vibration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As is well known (e.g., [1]), vibration and compressive loads are mechanical stimuli that have a powerful influence on living tissues. Recent studies in the E. Mamontov, V. Berbyuk Journal of Applied Mathematics and Physics animal models demonstrate that certain types of mechanical loads regulate various tissues.…”
Section: Introductionmentioning
confidence: 99%
“…7 -9 in [1] and the papers in [2]). One of the most well-known negative implications is hand-arm vibration syndrome (HAVS), or vibration-induced white finger (VWF).…”
Section: Introductionmentioning
confidence: 99%